Towards 2040: Collaborative approach in Finnish food systems transition - Kymalainen, Tiina; Tamlander, Tom; Ritala, Anneli; Seisto, Anu (Futures : the journal of policy, planning and futures studies, 2026)
This article presents experimental research that engaged Finnish stakeholders in discussions on how to transition global food systems toward sustainability by 2040, addressing urgent challenges such as climate change, resource depletion and population growth. The study introduces the “Future Food Court Workshops,” which involved representatives from various sectors, including industry, public institutions, third-sector organizations, educational entities, and consumers. To guide these discussions, the research developed an integrated framework combining social design, foresight, technology, and business perspectives, aiming to anticipate emerging needs and societal transformations. The workshops employed “Five Dimensions of Futures Consciousness” model for qualitative analysis of the stakeholder engagement; the model was used explicitly to understand how participants conceptualized the future of food systems. The analysis revealed, for example, how participants experienced sustainability challenges, their capacity for future-oriented behavior, the impact of present actions on future outcomes and the role of emerging technologies reflecting values of the systems they serve. This research advances the field of futures studies by demonstrating an interdisciplinary approach to engaging stakeholders in sustainable food system transitions, and hopefully offers valuable insights for researchers, policymakers, and practitioners, underscoring the necessity of adopting sustainable practices to address pressing environmental concerns. •Finnish stakeholders discussed sustainable food systems for the 2040 transition.•“Future Food Court Workshops” combined effectively foresight, social design, technology, and business approaches.•The analysis of the stakeholder engagement employed pragmatically the “Five Dimensions of Futures Consciousness" -model.•The selected emerging technologies were able to reflect values and address important sustainability challenges.•The results emphasize critical need for democratic decision-making and sustainable practices in food system transitions.